Figuratives in der auslandsdeutschen Pressesprache - Földes, Csaba (Kalbotyra, 2020)
This article is based on the understanding that figurative linguistic signs are in general a common research topic in the media language but represent a desideratum especially with regard to the German-speaking press abroad. Against this background, some of the figurative and formulaic related observations as well as the results of a current research project are thematised and discussed. The primary goal is a focused evidence-based analysis – more precisely: a theory-based qualitative exploration – of special features of figurative language use in three German-language minority newspapers from Russia, Kazakhstan and Hungary. In addition, manifestations of culturality are developed in the analysed media discourse, which is characterised by multilingualism and interculturality or rather transculturality. The approach is not normative and error-analytical, but descriptive and primarily contact- or intercultural-oriented. Among other things, it was found that the empirical database provided only relatively few figurative phrases. The findings include that other textual mechanisms prevail and due to the multilingual settings the text producers adopt fixed syntactic schemes from the contact languages. On the producer side, a German-based figurative language is generally used, but it is congruent with the figurativity of the respective contact language (in the present case: Russian, Kazakh and Hungarian), including Russian/Kazakh/Hungarian-oriented framings. In this context, the dominant feature is constituted of (virulent or latent) language contact-related phenomena with some dynamics: primarily transference formations of different kinds. At the same time, it cannot be ignored that the language and text (types) competence and especially the figurative competence of the text producers in the area of conceptual-writing skills vary widely and are often not comparable to those of federal German journalists.